2013
DOI: 10.1590/1414-431x20122477
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and biochemical markers of bone metabolism in patients with juvenile idiopathic arthritis

Abstract: Our objective was to evaluate the concentrations of serum 25-hydroxyvitamin D [25(OH)D], serum calcium, serum phosphorus, alkaline phosphatase, and parathormone (PTH) in patients with polyarticular juvenile idiopathic arthritis (JIA) and to associate them with disease duration and activity, bone mineral density and use of medications. In a cross-sectional and controlled study, 30 patients with polyarticular JIA were evaluated and compared to 30 healthy individuals matched for age and gender. Clinical status, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 31 publications
7
14
2
1
Order By: Relevance
“…It has to be pointed out that all those studies were done in high latitudes, including those on Florence and Rabat, meaning 42° and 32°N [15,27], respectively, as compared to the present study. Perhaps more striking, with regard to the importance of geographical variation, 25OHD levels in children from the state of São Paulo, Brazil (23°S), were reported as 25.7 ± 8.65 ng/mL [28] that are also lower to those found in our study, focusing on people living in a 4°S region of Brazil.…”
Section: Discussioncontrasting
confidence: 95%
“…It has to be pointed out that all those studies were done in high latitudes, including those on Florence and Rabat, meaning 42° and 32°N [15,27], respectively, as compared to the present study. Perhaps more striking, with regard to the importance of geographical variation, 25OHD levels in children from the state of São Paulo, Brazil (23°S), were reported as 25.7 ± 8.65 ng/mL [28] that are also lower to those found in our study, focusing on people living in a 4°S region of Brazil.…”
Section: Discussioncontrasting
confidence: 95%
“…No correlation between disease activity, type of JIA or metabolites of vitamin D. Control n = 28 Age, gender matched, hospitalized children 43.4 ± 40.7 nmol/L. Sao Paulo, Brazil Munekata et al 2013 23°S [ 25 ] JIA- polyarticular n = 30 (23F) 14 (4–20) 64.1 ± 21.6 High frequency of 25(OH)D deficiency in both control and JIA groups; no difference between the two. No association of 25(OH)D with disease activity.…”
Section: Results Of Scoping Review and Discussionmentioning
confidence: 99%
“…Of the 38 studies reviewed, six (15.8%) had mean 25(OH)D concentrations above 75 nmol/L [ 28 , 42 , 44 , 45 , 53 , 54 ]. Seventeen studies (44.7%) had mean 25(OH)D concentrations between 50 and 75 nmol/L [ 22 , 23 , 25 , 27 , 30 , 33 , 34 , 36 , 37 , 39 , 40 , 46 48 , 55 , 59 ] and 15 (39.5%) had values below 50 nmol/L [ 21 , 24 , 26 , 29 , 31 , 32 , 35 , 38 , 41 , 43 , 49 – 51 , 57 , 60 ]. Of those 15 studies, 10 reported the mean 25(OH)D value, the median value reported for one study and a range or cutoff was provided for four studies).…”
Section: Results Of Scoping Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of Raghu Nadhanan et al found that low dose of methotrexate can increase the risk of osteopenia [30]. But, other immunosuppressants such as Azathioprin, Chloroquine, Cyclophosphamide and Mycophenolat mofetil have no interference in bone mass density [31][32][33].…”
Section: Discussionmentioning
confidence: 99%